Proceedings of the 21st ACM International Conference on Multimedia 2013
DOI: 10.1145/2502081.2502280
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the multimedia unconscious

Abstract: One of the main findings of cognitive sciences is that automatic processes of which we are unaware shape, to a significant extent, our perception of the environment. The phenomenon applies not only to the real world, but also to multimedia data we consume every day. Whenever we look at pictures, watch a video or listen to audio recordings, our conscious attention efforts focus on the observable content, but our cognition spontaneously perceives intentions, beliefs, values, attitudes and other constructs that, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(16 citation statements)
references
References 45 publications
0
12
0
4
Order By: Relevance
“…Im Gegensatz hierzu scheint gerade die Vielzahl verschiedener Reize in Bildern interessant, wie wir ihnen im täglichen Leben immer wieder begegnen. Dafür spricht, dass Persönlichkeitseigenschaften neben inhaltlichen und ästhetischen Reizen in Bildern durch eine Vielzahl weiterer Reize angesprochen werden (Van Der Heide, D'Angelo & Schumaker, 2012) und Personen implizite Informationen aus Bildern ableiten, wie beispielsweise Werte und Einstellungen (Cristani, Vinciarelli, Segalin & Perina, 2015). Die genannten Studien zur Vorhersage von Persönlichkeitseigenschaften anhand normaler Fotos aus sozialen Netzwerken zeigen, dass auch komplexe Bilder Informationen über Persönlichkeitseigenschaften beinhalten.…”
Section: Theoretischer Hintergrundunclassified
“…Im Gegensatz hierzu scheint gerade die Vielzahl verschiedener Reize in Bildern interessant, wie wir ihnen im täglichen Leben immer wieder begegnen. Dafür spricht, dass Persönlichkeitseigenschaften neben inhaltlichen und ästhetischen Reizen in Bildern durch eine Vielzahl weiterer Reize angesprochen werden (Van Der Heide, D'Angelo & Schumaker, 2012) und Personen implizite Informationen aus Bildern ableiten, wie beispielsweise Werte und Einstellungen (Cristani, Vinciarelli, Segalin & Perina, 2015). Die genannten Studien zur Vorhersage von Persönlichkeitseigenschaften anhand normaler Fotos aus sozialen Netzwerken zeigen, dass auch komplexe Bilder Informationen über Persönlichkeitseigenschaften beinhalten.…”
Section: Theoretischer Hintergrundunclassified
“…Важным показателем является и степень согласованности экспертов-психологов, проводивших исследования. Однако только в работе [7] был проведен анализ степени согласованности, которая, тем не менее, оказалась весьма низкой.…”
Section: обсуждение результатовunclassified
“…Biel et al [3] used Youtube vloggers video frames to estimate personality impressions using facial expressions and the Big-Five traits. Likewise, Cristani et al [11] showed that images in which the users "favorite" on Flickr enables the prediction of both apparent and actual (self-assessed) personality traits of Flickr users. Again, Vernon et al [58] investigated the effects of several physical attributes, for instance, the head size, posture, and chin-length on person's impressions.…”
Section: Introductionmentioning
confidence: 99%